Pendampingan Sistem Informasi Arsip Surat sebagai Upaya Peningkatan Kinerja Administrasi di Kecamatan Kota Kudus - Neila Mei Ika Suryani; Anteng Widodo (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
The process of managing correspondence at the District Office of the City is still carried out manually using notebooks and paper disposition sheets. This condition makes the recording of letters, dispositions, and document searches inefficient and time-consuming. This situation could lead to the loss of archive documents and delays in conveying information to the relevant departments. Based on these issues, there is a need for information that can support digital letter management. This web-based information system is designed to simplify the recording of incoming and outgoing letters, letter disposition management, and digital document archiving to make it more organised and easily accessible. The implementation of this community service activity uses a qualitative approach, including needs analysis, system design, system implementation and testing, system maintenance, as well as monitoring and evaluation. This system was built using the Laravel framework and MySQL as the database. The results show that it can help make managing incoming and outgoing letters, dispositions, and filing digitally much easier. The digital archive search feature speeds up the process of finding documents, reducing the time from 8-10 minutes to less than 2 minutes. Evaluation also shows that users find the system easier to use and more effective for searching archives compared to the previous manual method. So, implementing this web-based letter management and disposition information system can improve the quality of letter administration and boost performance at the District Office more efficiently and effectively.